Analisis Peluang Kredit Lancar Studi Kasus: PT. Pegadaian Area Padang - Fahmi Agusman; Joan Marta (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
The purpose of this research to find out how the influence of Customer Characteristics, Business Characteristics, and Credit Characteristics on Current Loans at PT. Pegadaian Area Padang. The factors used are customer characteristics (gender, age, education, marital status, and number of dependents), business characteristics (business field, ownership of business premises, length of business, and income), and credit characteristics (loan value, product, and installment ratio). This research uses logistic regression analysis method. The variables of trading business, loan value, Flexi product, and installment ratio have a significant influence on the chances of a customer's current credit at PT. Pegadaian Area Padang. Meanwhile, the variables of gender, age, education, marital status, number of dependents, ownership of place of business, length of business, and income do not have a significant influence on the chances of a customer's current credit at PT. Pegadaian Area Padang.